Survey of viruses belonging to different genera and species in noble garlic in Brazil (Scientia Agricola, 2015)
Garlic (Allium sativumL.) is a host to several viruses, most commonly those belonging to theAllexivirus,Carlavirus, orPotyvirusgenera. Nine species distributed among these three genera have been reported in Brazil: two species within carlaviruses, two within potyviruses, and five within allexiviruses. To quantify the prevalence of these viruses, young leaves from 520 plants (plants either symptomatic or asymptomatic) were collected from commercial fields grown in four Brazilian states and analyzed using universal and species-specific primers via the reverse transcription polymerase chain reaction (RT-PCR). Potyvirus presence was positive in 306 samples (81 %), 151 of them (38 %) in mixed infections with other viruses. The most frequent potyviruses wereOnion yellow dwarf virus(OYDV, 56 %) andLeek yellow stripe virus(LYSV, 55 %). 187 samples (49 %) were positive for allexivirus, with 33 (9 %) showing single infections and 154 (41 %) showing mixed infections withGarlic virus A (GarV-A),Garlic virus B(GarV-B),Garlic virus C(GarV-C),Garlic virus D(GarV-D), and species belonging to theCarlavirus andPotyvirusgenera. The predominant species in which allexiviruses were found were GarV-A and GarV-D. Only 15 samples (4 %) were infected solely by a carlavirus, and 63 (17 %) showed mixed infections with viruses from different genera. The dominant species of carlavirus wasGarlic commom latent virus(GarCLV). Carlaviruses and allexiviruses are frequently associated with mixed infections with potyviruses, whereas mixed infections with carlaviruses and allexiviruses are rare. About 70 % of the plants collected were positive for at least one species of virus.